A “Cultural” Renaissance: Genomics Breathes New Life into an Old Craft - Paul Carini (mSystems, 2019)
ABSTRACT Sometimes, to move ahead, you must take a look at where you have been. Culturing microbes is a foundational underpinning of microbiology. Before genome sequencing, researchers spent countless hours tediously deducing the nutritional requirements of bacterial isolates and tinkering with medium formulations to entice new microbes into culture. This art of cultivation took a back seat to the powerful molecular tools of the last 25 years, and as a result, many researchers have forgotten the utility of having a culture in hand. This perception is changing, as there is clearly a renewed interest in isolating microbes from various environments. Here, I suggest three focus areas to ensure continued growth and success of this “cultural” renaissance, including (i) setting clear cultivation goals, (ii) funding exploratory cultivation, and (iii) culturing and studying unusual organisms. “Unculturable” is a frame of mind, not a state of microbiology; it is time to dust off the bottle of yeast extract.